The role of Section 12 A (3) of the Competition Act to bring into effect the objectives of the act of addressing social and economic problems and past inequalities through the public interest assessment in merger proceedings - Mgiba, Martin Rifuwo (Department of Commercial Law, 2015)
The advent of our constitution necessitated a drastic re-evaluation of our aspirations as a young democratic state. Formal equality had to be accompanied by substantive equality. Substantive equality could only be achieved by a total revamp of our economic policy and framework, which was designed to benefit the white minority. The government quickly realized the fact that our competition jurisprudence had a significant role to play in bringing about economic and social reform. The challenge however was that the economy inherited, was littered with monopolies. As a result in 1995, the South African government embarked on a project to review competition policy and the process was concluded in September 1998 when Parliament passed the Act into law. The Act introduced new provisions, including the consideration of public interest in merger regulation. The inclusion of public interest in the Act was motivated by the need to address the socio-economic inequalities arising in society. Competitiveness and development was seeing as mutually supporting objectives. It was recognised that a small economy like South Africa, may be concentrated and therefore any merger and acquisition activity can create further concentration and social disparities if left unchecked. Mergers may lead to the shedding of jobs, especially where they are driven by cost saving and efficiency goals. Hence, it was recognised as being important that merger regulation consider the preservation of jobs where these arise as a result of the merger. In an economy with high unemployment rates, it would not serve the public interest to encourage or allow further job losses. Hence the inclusion of section 12 A 3 of the Competition Act which made it mandatory to consider public interest considerations in merger proceedings. This paper seeks to evaluate if competition authorities have carried out their mandate of addressing socio economic issue in merger processing through section 12 A (3).